The Influence of Leadership Style and Work Motivation on Employee Performance at the Regional Office of the Directorate General of Immigration in Riau Province - Lince Lestaria; Meizy Heriyanto; Sri Sediyaningsih (Publik : (Jurnal Ilmu Administrasi), 2025)
This study investigates the influence of transformational leadership style and work motivation on employee performance at the Regional Office of the Directorate General of Immigration in Riau. The research was conducted to understand how leadership behavior and motivational factors contribute to improving individual and organizational performance within the public sector. The study employed a quantitative approach using a questionnaire distributed to employees, and the data were analyzed through multiple linear regression. The results indicate that transformational leadership has no significant direct effect on employee performance (t = –1.516, Sig. = 0.139 > 0.05), suggesting that the implementation of transformational values such as inspiration, individual consideration, and empowerment remains limited. In contrast, work motivation shows a positive and significant effect on performance (t = 3.685, Sig. = 0.001 < 0.05), emphasizing that both intrinsic and extrinsic motivation enhance commitment and productivity. Simultaneously, transformational leadership and work motivation together significantly affect performance (F = 9.797, Sig. = 0.000 < 0.05) with a determination coefficient (R²) of 0.380. This means that 38% of performance variation is explained by both variables, while 62% is influenced by other factors. The study concludes that developing strong work motivation supported by effective leadership behavior is essential to optimizing employee performance in government institutions.